2011
DOI: 10.1007/s00264-011-1264-0
|View full text |Cite
|
Sign up to set email alerts
|

Forty-five-degree or higher insertion angles are required to penetrate the opposite cortex in bicortical applications of Kirschner wires: an in vitro study on sheep bones

Abstract: Purpose Slippage of the wires over the opposite cortex from the endosteal side is frequent and can lead to insufficient stability. This in vitro biomechanical study was planned to investigate the angle of wire insertion that leads to trans cortex perforation. Methods Long bones of sheep were cut longitudinally into two pieces and half bones were stabilised on a frame. Three orthopaedic surgeons performed the experiment using ten wires of four different diameters at two different drilling speeds. Each wire was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Cadaver investigations of two divergent 60-degree K-wire configurations showed that it failed to obtain bicortical purchase and bounced off the far cortex [39]. The tendency of bending and skidding over the opposite cortex was observed, resulting in the replacement of K-wire with a thicker fixation material [40]. Although 3 wire fixation showed the best stability, occasionally, fixation of 3 wires can encounter technical difficulty in the real clinical situation because 6 years old children have limited bone area.…”
Section: Discussionmentioning
confidence: 99%
“…Cadaver investigations of two divergent 60-degree K-wire configurations showed that it failed to obtain bicortical purchase and bounced off the far cortex [39]. The tendency of bending and skidding over the opposite cortex was observed, resulting in the replacement of K-wire with a thicker fixation material [40]. Although 3 wire fixation showed the best stability, occasionally, fixation of 3 wires can encounter technical difficulty in the real clinical situation because 6 years old children have limited bone area.…”
Section: Discussionmentioning
confidence: 99%
“…Also during drilling, if the angle is kept more than 45° measuring from the horizontal articular surface (also called the minimal critical angle), it avoids slippage of the wires over the opposite cortex. The study observed that wires perforate easily and pass opposite cortices when inserted at ≥45° [ 10 ]. Lobst et al have reported that when a smaller diameter wire was used at lower inclinations, the angle of contact with the far cortex may be large causing the wire not to penetrate the cortex and leading to slippage of the wire tip over the endosteal surface of the opposite cortex.…”
Section: Discussionmentioning
confidence: 99%